Studies on anti-inflammatory activity and wound-healing property of secondary metabolite of Anredera cordifolia (Ten.) Steenis leaves: A review - Desak Made Nita Pratiwi, Sri Hartati Yuliani, Putu Oka Samirana (Journal of Applied Pharmaceutical Science, 2025)
Anredera cordifolia (Ten.) Steenis is a medicinal plant of Indonesia that belongs to the genus Anredera and the family Basellaceae. Scientifically, the leaf of A. cordifolia (Ten.) Steenis has antibacterial, antioxidant, anti-inflammatory, and wound-healing properties. Anredera cordifolia (Ten.) Steenis leaves have secondary metabolite content that plays a crucial role in eliciting observed pharmacological effects. This article discusses the secondary metabolite content, which actively plays a role in anti-inflammatory and wound-healing activity. The literature research is conducted through PubMed and Google Scholar databases. In general, the secondary metabolites found in the extracts of the leaves of A. cordifolia (Ten.) Steenis are flavonoids, alkaloids, tannins, steroids, triterpenoids, and saponins. Research on anti-inflammatory activity includes in vitro, in vivo, and clinical studies on the inhibition of inflammatory cytokines, as well as in silico studies on mechanisms to inhibit cyclooxygenase-2. Meanwhile, the discussion on wound-healing activities encompasses the healing of incision/excision wounds, infected wounds, diabetic wounds, burns, and post-surgery wounds. Although the information on anti-inflammatory andwound-healing properties can be used to develop innovative traditional medicines, there is currently a dearth of information regarding the function of secondary metabolites.
Keywords: Anredera cordifolia (Ten.) Steenis leaves, secondary metabolite, anti-inflammatory, wound healing